34.5k views
2 votes
F(x)=-x-4 solve when f(x)=6

User Dontexist
by
5.8k points

2 Answers

3 votes

Answer:

2

Explanation:

Since f(x) is 6, we can plug that into the equation:

6-4,

which gives us 2

User Mariozawa
by
6.0k points
4 votes

Answer: Pretty sure the answer is -10

Step-by-step explanation: If you replace f(x) with 6, you can figure out the answer more quicker.

6 = -x-4

10 = -x

x=-10

User Braden Becker
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.